1997
DOI: 10.1161/01.atv.17.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Isolated From Human Atherosclerotic Plaques Produce IL-8, and Oxysterols May Have a Regulatory Function for IL-8 Production

Abstract: Oxysterols are biologically active molecules generated during oxidation of LDL. Several of these oxysterols were found in macrophage-derived foam cells from human atherosclerotic tissue (eg, 7-hydroxycholesterol, 7-ketocholesterol, 5-epoxycholesterol, and 25-hydroxycholesterol). A specific stimulation of interleukin-8 (IL-8) production by oxidized LDL (oxLDL) has been shown by other investigators. In foam cells from human atherosclerotic tissue, we found high levels of IL-8 (183.1 pg/10(6) cells) compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 36 publications
6
104
0
2
Order By: Relevance
“…Under in vivo conditions, the oxysterols are always present together with a very high excess of cholesterol, and this cholesterol may decrease or prevent the activity of the oxysterol ( 31 ). It has been reported that 25-hydroxycholesterol induces production of interleukin 1 ␤ and interleukin 8 from human macrophages ( 32,33 ). It cannot be excluded that a local interleukin release as a consequence of the high levels of 25-hydroxycholesterol may be of pathogenetic importance in the SPG5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Under in vivo conditions, the oxysterols are always present together with a very high excess of cholesterol, and this cholesterol may decrease or prevent the activity of the oxysterol ( 31 ). It has been reported that 25-hydroxycholesterol induces production of interleukin 1 ␤ and interleukin 8 from human macrophages ( 32,33 ). It cannot be excluded that a local interleukin release as a consequence of the high levels of 25-hydroxycholesterol may be of pathogenetic importance in the SPG5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of lipoproteins [25,26] in the arterial wall initiates the early stage of atherosclerosis. This is then followed by activation of endothelial expression of adhesion molecules [27][28][29], development of cholesterol-laden foam cells [30,31] and formation of atherosclerotic plaque [32][33][34]. The gly- cated lipoprotein(s) affects LDL receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular accumulation of 7-ketocholesterol leads to increased production of reactive oxygen species and induces apoptosis in various cell types, including macrophages, endothelial cells, and smooth muscle cells (12)(13)(14)(15). In addition, oxysterols induce inflammatory gene expression in monocytemacrophages (34)(35)(36)(37). Therefore, 7-ketocholesterol and related oxysterols probably have an important role in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%